Low-Grade Central Osteosarcoma of the Rib: A Case Report and Brief Review of the Literature - Mana Moghadamfalahi; Houda Alatassi (Case Reports in Pathology)
Low-grade central osteosarcoma is a rare variant of osteosarcoma which comprises less than 1-2% of all osteosarcomas. Most low-grade osteosarcomas involve long bones, most commonly distal femur, and proximal tibia. Histologically this tumor is difficult to diagnose, and an unusual location makes this diagnosis even more challenging. Here we report a case of low-grade osteosarcoma presenting as a chest wall mass involving the left 6th–8th ribs. This unusual site of presentation significantly added to the diagnostic difficulties of this rare tumor with challenging histologic features. To the best of our knowledge, only six cases of low-grade central osteosarcoma of the ribs have been reported in the English literature.